The woman in Jano film posters from 1940-1970 - García García, Mª Azucena; López Alarma, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Francisco Fernández-Zarza Pérez, known as Jano, was a multifaceted artist in the world of advertising and film. He stood out for his versatility when portraying film stars belonging to the national and international “star-system” during the postwar period and the Spanish transition. Starting from the importance of the poster as a means of transmitting the message, we intend to discover if its posters, between the years 1940 and 1970, in addition to acting as a claim to publicize the films, also acted as a reflection of social stereotypes through the representation of the female roles.